Role of pyrophosphate on the degradation of sulfamethoxazole by permanganate combined with different reductants: Positive or negative. (24th October 2019) - Liu, Weifan; Yin, Daqiang; Guan, Xiaohong; Rao, Dandan; Cao, Guomin; Sun, Yuankui
Abstract: Activating permanganate with reductants has gained increasing attention recently for efficient organic contaminants abatement via reactive intermediate Mn species. However, few studies have been conducted to explore the role of pyrophosphate (PP), a typical complexing agent for intermediate Mn species, in activated permanganate systems. In this study, taking sulfamethoxazole (SMX) as a probe compound, the influences of PP on SMX degradation by permanganate/thiosulfate and permanganate/hydroxylamine were extensively studied. It was found that both thiosulfate and hydroxylamine were able to activate permanganate for oxidation of SMX in the absence of PP. However, upon the introduction of PP, opposite effects were observed in the two systems where PP further improved the activation of permanganate by thiosulfate but dampened the performance of permanganate/hydroxylamine markedly. For permanganate/hydroxylamine system, MnO2 was determined to be the only reactive oxidative species accounting for SMX degradation in the absence of PP, and its generation could be completely inhibited by PP. While in permanganate/thiosulfate system, both Mn(V) and MnO2 were responsible for SMX oxidation, and the introduction of PP could strengthen the oxidative ability of Mn(V). These results could shed some insights on the suitability of applying PP to explore the kinetics and mechanisms of manganese involved redox reactions. Practitioner points: Both Na2 S2 O3 and NH2 OH·HCl can activate KMnO4 for SMX removal without PP. MnO2 is the reactive oxidative species involved in KMnO4 /NH2 OH·HCl system. Mn(V) and MnO2 account for the SMX oxidation by KMnO4 /Na2 S2 O3 system. PP could inhibit the formation of MnO2 but enhance the oxidative ability of Mn(V). Abstract : The influence of pyrophosphate (PP) on the pathways of permanganate‐centered redox reactions was systematically investigated. Results indicated that, in thiosulfate/permanganate and hydroxylamine/permanganate systems, the reactive oxidative species accounting for contaminants removal could change upon the addition of PP. Hence, special attention should be paid when PP was employed to identify reactive Mn intermediates.